Melanin Production Inhibitors from the West African Cassipourea congoensis - Takou, Dieudonné M.; Waffo, Alain F. Kamdem; Langat, Moses K.; Wansi, Jean D.; Mulcahy-Ryan, Lauren E.; Schwikkard, Sianne L.; Opara, Elizabeth I.; Mas-Claret, Eduard; Mulholland, Dulcie A. (Planta Medica International Open, 2019)
Cassipourea congoensis (syn. Cassipourea malosana) is used in African countries as a skin-lightening agent. Two previously unreported cycloartane triterpenoids, 26-hydroxy-3-keto-24-methylenecycloartan-30-oic acid 1 and 24-methylenecycloartan-3β,26,30-triol 2 along with the known mahuannin B 3, 7-methoxymahuannin B 4, 7-methoxygeranin A 5, methyl-3-(4-hydroxy-3-methoxyphenyl)-2E-propenoate, glycerol-1-alkanoate, (E)-3-(4-hydroxy-3-methoxyphenyl)prop-2-enal 6, (-)-syringaresinol 7, and stigmast-5-en-3-O-β-D-glucoside, were isolated from the roots of C. congoensis. The crude extract and compounds 1 and 5 were found to inhibit the production of melanin at 10 µM with low cytotoxicity validating the ethnomedicinal use of this plant.
Keywords: Cassipourea congoensis; rhizophoraceae; cycloartane triterpenoids; 26-hydroxy-3-keto-24-methylenecycloartan-30-oic acid; 24-methylenecycloartan-3β; 26; 30-triol; skin-lightening agents; tyrosinase inhibition and melanin inhibition